Dignidade da pessoa humana : o acesso à justiça como direito fundamental e a admissibilidade da testemunha técnica no âmbito dos juizados especiais da Lei 9.099, de 1995 - Chianca, Hugo de Barros (2013)
The present work has the objective of demonstrating the admissibility of the institution of the technical witness, widely used by North American law, in the specialized procedure inscribed by Law 9.009, of 1995, as an immediate way of accomplishing the fundamental right of access to justice, and, in a mediate way, as the materialization of the principle of human dignity protection. The Federal Constitution, of 1988, imposes the necessary observance of the fundamental principle in comment, imposing a roll of fundamental rights which, in their essence, aim to assure the enforcement of that commandment. Among the fundamental rights we mentioned, some of them apply in a direct way to processual relations. In this sense, the fundamental right of access to justice emerges with the scope of providing the necessary resources to the attainment of an adequate jurisdictional guardianship, useful and just, by means of a process which, from its instrumental nature, promotes the accomplishment of that purpose. The creation of specialized procedures turns out as the manifestation of the mentioned fundamental right, and, thus, the law of special courts strengthens that commandment. However, in virtue of the orality principle, the evidential production in this procedure suffers certain restrictions, which make it impossible the accomplishment of proof that compromisse the reasonable duration of the procedure, established within the framework of the maxim of orality. Therefore, this work has as object the demonstration of the admissibility of the institution of the technical witness in the specialized procedure of Law 9.009, of 1995, in view of the need of accomplishing the fundamental right of access to justice. For the making of this dissertation we used bibliographical research, including national and foreign doctrines, as well as national jurisprudence.